Talon Cusp in A Supplementary Tooth - A Case Report - S Meera; Babu Mathew (Wolters Kluwer Medknow Publications, 2005)
Talon cusp is a morphological dental anomaly, which presents as an accessory cusp and commonly occurs on the lingual surfaces of the incisors. Supernumerary tooth is a common dental anomaly, which occurs in both maxilla and the mandible. Supernumerary teeth in the deciduous dentition is less common than in the permanent dentition. Talon cusp in a supernumerary tooth is an uncommon dental anomaly. A case of this uncommon anomaly is presented in this article.